Pelatihan Siaga Bencana Pada Anak Sekolah Dasar Di SD N 7 Labuan Baru Mamboro Palu Utara - Metrys Ndama; Nurlailah Umar; Ismunandar Ismunandar; I Ketut Suardana (Jurnal Pengabmas Masyarakat Sehat, 2019)
The earthquake, tsunami, and liquefaction natural disasters that occurred in Palu, Sigi Biromaru on September 28, 2018, were national disasters that infrastructure affected the buildings including schools. Besides the psychological impact on school children. Labuan Baru Public Elementary School is located not far from the coast of the tsunami. For this reason, it is necessary to conduct earthquake and tsunami disaster preparedness training for school children. The purpose of this service is to improve the ability of students of SDN 7 Labuan Baru about earthquake and tsunami natural disaster preparedness in school-based disaster management. The target of this activity is 100 SDN Labuan Baru students grade IV-VI totaling 100 people. The service was held on November 24, 2018, which involved a dataset from the Poltekkes Kemenkes Denpasar and also involved D-III students in Palu Nursing and D-IV Palu Nursing. The training method is a lecture conducted in a tent and a simulation conducted in an open field. After the training has been carried out, students know what to do when an earthquake occurs, which is protecting the head with their hands or hiding under a table, away from the glass, and running to an open or higher place. For SDN 7 Labuan Baru schools, they can prepare evacuation marks/routes and gathering points when a disaster occurs.Keywords: Disaster safe school, disaster preparedness training, school childrenThe earthquake, tsunami and liquefaction natural disasters that occurred in Palu, Sigi Biromaru on September 28, 2018 were national disasters that infrastructure affected the buildings including schools. Besides the psychological impact on school children. Labuan Baru Public Elementary School is located not far from the coast of the tsunami. For this reason, it is necessary to conduct earthquake and tsunami disaster preparedness training for school children. The purpose of this service is to improve the ability of students of SDN 7 Labuan Baru about earthquake and tsunami natural disaster preparedness in school-based disaster management. The target of this activity is 100 SDN Labuan Baru students grade IV-VI totaling 100 people. The service was held on November 24, 2018, which involved a detaser from the Poltekkes Kemenkes Denpasar and also involved D-III students in Palu Nursing and D-IV Palu Nursing. The training method is a lecture conducted in a tent and a simulation conducted in an open field. After the training has been carried out, students know what to do when an earthquake occurs, which is protecting the head with their hands or hiding under a table, away from the glass, and running to an open or higher place. For SDN 7 Labuan Baru schools, they can prepare evacuation marks / routes and gathering points when a disaster occurs.Keywords: Disaster safe school, disaster preparedness training, school children